K-groups with finite coefficients and arithmetic - Østvær, Paul Arne (MATHEMATICA SCANDINAVICA, 2003)
In this paper we prove rank formulas for the even K-groups of number rings and relate Leopoldt’s conjecture to K-theory. These results follow from a computation of the higher K-groups with finite coefficients.